Intermittent Loss of Telemetry Data: Lessons From a Leadless Pacemaker - Katsaras, Dimitrios (JACC Case Rep, 2021)
We present the case of a 63-year-old female patient who presented to the pacemaker clinic for a scheduled interrogation of her leadless pacemaker. The device interrogation was suggestive of intermittent under-sensing with failure to pace. Connecting the electrocardiogram lead to the pacing system analyzer raised the suspicion of intermittent loss of telemetry data. (Level of Difficulty: Beginner.)